Lithium ion battery positive electrode material and preparation method thereof

By designing the matrix and interface of the positive electrode material of the lithium-ion battery, the doping and cladding layer of specific elements is used to form an interface barrier layer, which solves the problem of surface structure deterioration under high voltage, improves the charging and discharging performance of the material and the circulation of the battery life.

CN119252902APending Publication Date: 2025-01-03QINGHAI TAIFENG XIANXING LITHIUM ENERGY TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411493240.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The surface structure of the existing lithium-ion battery cathode material deteriorates at high voltage, resulting in an increase in battery impedance and a decrease in the efficiency of lithium-ion embedding and disengagement, affecting the energy density and cycle life of the material.

Method used

Using a coordinated matrix and interface design, through collaborative structural modification of specific elements at the matrix and interface, the doping of M elements and the cladding layer are enriched within the preset depth of the matrix interface to form an interface barrier layer and prevent packets. The diffusion of overlay elements improves the stability of the interface structure.

Benefits of technology

It effectively improves the charging and discharging performance of the positive electrode material of lithium-ion battery under high voltage, improves the stability of the interface structure, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252902A_ABST
    Figure CN119252902A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery positive electrode material and a preparation method thereof, and belongs to the technical field of batteries. The lithium ion battery positive electrode material is a lithium-containing composite oxide composed of a matrix and a coating layer. According to the preparation method disclosed by the invention, through collaborative substrate and interface design, collaborative structure modification of specific elements at the substrate and the interface can be realized, so that the interface structure stability of the material can be effectively improved while the stable performance of the high-voltage substrate structure is given into consideration, and the charge-discharge performance of the positive electrode material of the lithium ion battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] As a rechargeable secondary battery, lithium-ion batteries have been widely used in digital electronic products such as notebooks and mobile phones due to their high energy density, low self-discharge, and long cycle life. A key factor currently restricting the development of electric vehicles is that their range cannot meet people's living needs. Therefore, it is becoming more and more urgent to develop high-energy-density lithium-ion battery positive electrode materials. High voltage is an effective way to increase the energy density of positive electrode materials. However, positive electrode materials face the problem of surface structure degradation under high voltage, which causes a significant increase in the impedance of the battery, resulting in a large number of lithium ions that cannot be effectively embedded and removed from the material, thereby causing the material's capacity and cycle performance to decrease.

[0003] In order to solve the problem of structural degradation of positive electrode materials under high voltage, common means include bulk doping, gradient doping and surface coating CN111435744A, etc. The patent application number CN03822891.2 "Positive electrode material for lithium secondary battery and its manufacturing method" mainly uses lithium cobalt oxide doped with aluminum or magnesium, fluorine and group IV transition metal elements, and emphasizes that the doping elements are uniformly present near the surface of the particles. The patent publication number CN103354958B designs a positive electrode active material with a full particle concentration gradient, wherein the concentrations of M1, M2 and M3 in the positive electrode active material present a continuous concentration gradient in the entire area from the particle core to the surface part, but this solution may cause elements to diffuse mutually at higher temperatures, and the concentration gradient cannot be maintained. Patent publication number CN105336915B discloses a powder particle, including a bulk phase portion and a coating portion coated on the outer surface of the bulk phase portion, the bulk phase portion has electrochemical activity and high charge and discharge capacity, the coating portion has no electrochemical activity or has a very low charge and discharge capacity, but the coating portion designed in this scheme will reduce the energy density of the material and cannot effectively stabilize the interface structure by surface doping of the structure and achieving the diffusion depth of the surface coating elements.

[0004] It can be seen that common doping and coating methods are difficult to effectively solve the problem of surface structure degradation of positive electrode materials under high voltage. For example, gradient doping, although the doping content can be gradually reduced or increased from the surface to the inside through the precursor stage, after the material is sintered at high temperature, the doping elements tend to be homogenized under the drive of the concentration gradient, and the effect of gradient doping cannot be achieved. Core-shell structure materials also have similar problems. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings, the present invention provides a lithium-ion battery positive electrode material, which can achieve coordinated structural modification of specific elements at the matrix and the interface through coordinated matrix and interface design, thereby effectively improving the interface structure stability of the material while taking into account the high voltage matrix structure stability performance, thereby improving the charge and discharge performance of the lithium-ion battery positive electrode material.

[0006] Another object of the present invention is to provide a method for preparing a positive electrode material for a lithium ion battery.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A lithium-ion battery positive electrode material, which is a lithium-containing composite oxide with a general formula of Li α Ni x Co y M z O 2-β N β , consisting of a substrate and a coating layer, wherein M is selected from at least one element of Co, Al, Mn, Ti, Zr, Sr, W, B, Mg, Y, La, Ta, and Nb, a part of the M element is used as a doping element of the substrate, and the other part is used as a coating element of the coating layer and is enriched within a preset depth of the substrate interface; N is selected from at least one element of P and F; 0.95≤α≤1.05, 0.0≤x≤0.70, 0≤y<1.0, 0≤z≤0.3, 0≤β≤0.05.

[0009] Furthermore, M is selected from +4 or higher valence elements (M n+ , at least one of n≥4).

[0010] Furthermore, the doping amount of the Ni element is 0.05≤x≤0.25.

[0011] Furthermore, the M element is mainly enriched in the depth range of 0-5 μm at the matrix interface.

[0012] A method for preparing a positive electrode material for a lithium ion battery comprises the following steps:

[0013] 1) preparing a compound containing Ni, Co, and M elements, mixing the compound with a lithium source, performing step-wise temperature-raising sintering after the mixture is evenly mixed, and then cooling to room temperature to obtain a positive electrode matrix material;

[0014] 2) preparing an additive containing Co and M elements;

[0015] 3) The obtained positive electrode matrix material and the additive containing Co and M elements are dry-mixed or liquid-mixed, wherein the liquid phase is evenly mixed and then dried to achieve M element coating, and the dried material obtained after mixing is sintered in stages at a high temperature, and then cooled to room temperature to obtain the positive electrode material for lithium-ion batteries.

[0016] Furthermore, the compound containing Ni, Co and M elements in step 1) is one of the hydroxides, oxides, fluorides, carbonates, nitrates, acetates and alkoxides containing Ni, Co and M elements, wherein the co-precipitated hydroxide, fluoride, carbonate, nitrate, acetate or alkoxide containing Ni, Co and M elements is prepared by a co-precipitation method, and the oxide is obtained by sintering the co-precipitate under air or oxygen.

[0017] Furthermore, in step 1), the compound and the lithium source are mixed according to a molar ratio of lithium to all metal elements of 0.95-1.05.

[0018] Furthermore, the conditions for the staged temperature rising sintering in step 1) are: in an air or oxygen atmosphere, first rise from room temperature to the first insulation section at a rate of 1-5°C / min, with an insulation temperature of 400-700°C and an insulation time of 1-5h; then rise from the first insulation section to the second insulation section at a rate of 1-3°C / min, with an insulation temperature of 800-1100°C and an insulation time of 5-15h; then cool from the second insulation section to the third insulation section at a rate of 1-20°C / min, with an insulation temperature of 600-800°C and an insulation time of 1-5h.

[0019] Furthermore, in step 1), the first heat preservation stage is sintered in an atmosphere with an oxygen content of ≤0.8 standard oxygen partial pressure.

[0020] Furthermore, the additive containing Co and M elements in step 2) is any one of nano hydroxides, nano carbonates and nano oxides containing Co and M elements and uniformly distributed, preferably hydroxides.

[0021] Furthermore, in step 3), a compound containing a lithium source or at least one of M and N is first mixed with an additive containing Co and M elements to obtain a first mixture, wherein the molar ratio of Li element to M element in the first mixture is 0.0 to 2.0, and then the first mixture is mixed with a positive electrode matrix material to obtain a second mixture.

[0022] Furthermore, the conditions for the staged temperature rising sintering in step 3) are: in an air or oxygen atmosphere, first rise from room temperature to the first insulation section at a rate of 1-5°C / min, with an insulation temperature of 400-700°C and an insulation time of 1-5h; then rise from the first insulation section to the second insulation section at a rate of 1-3°C / min, with an insulation temperature of 700-950°C and an insulation time of 1-15h; then cool from the second insulation section to the third insulation section at a rate of 1-20°C / min, with an insulation temperature of 600-800°C and an insulation time of 1-5h.

[0023] Furthermore, in step 3), the atmosphere for the staged temperature-raising sintering is an oxygen atmosphere, which can more effectively oxidize the M element to a high-valence state, thereby making it more difficult for the coating element M to enter the material matrix.

[0024] The beneficial effects achieved by the present invention are as follows:

[0025] The inventors have found that the structural degradation of positive electrode materials generally starts from the surface interface, especially when the voltage gradually increases or the amount of lithium removal gradually increases, the surface structure is more severely damaged. Therefore, the present invention designs the interface of the matrix or its near surface and the sintering process for the positive electrode material, pre-forms an interface element barrier layer, and utilizes the strong bond energy between elements or the repulsive effect formed when a large amount of doping elements M already exist in the matrix to hinder the further diffusion of the coating element M into the matrix, making it difficult for the coating element M to enter the material matrix and form interface enrichment. This structure improves the stability of the interface structure of the positive electrode material, thereby improving the electrochemical performance of the positive electrode material under high voltage or high lithium removal. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the lithium-ion battery positive electrode material sample of Example 1.

[0027] Figure 2 This is a SEM image of the lithium-ion battery positive electrode material sample of Comparative Example 1.

[0028] Figure 3 EPMA image of the element Mn in the lithium-ion battery positive electrode material sample of Example 1.

[0029] Figure 4 EPMA image of the element Mn in the lithium-ion battery positive electrode material sample of Comparative Example 1. DETAILED DESCRIPTION

[0030] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.

[0031] Example 1

[0032] 1) Preparation of positive electrode matrix material

[0033] Preparation of Ni by co-precipitation method 0.09 Co 0.9 Mn 0.01 (OH)2, in which Ni and Co are evenly distributed Ni 0.09 Co 0.9 Mn 0.01 In the (OH)2 matrix, Mn is only distributed in the Ni 0.09 Co 0.9 Mn 0.01 (OH)2 surface 0-5μm.

[0034] Take lithium carbonate and Ni 0.09 Co 0.9 Mn 0.01 (OH)2, mixed according to the molar ratio of lithium to metal of 1.05, the mixed raw materials were heated from room temperature to the first insulation section at 5°C / min, the insulation temperature was 700°C, and the insulation time was 1h; the temperature was raised from the first insulation section to the second insulation section at 3°C / min, the insulation temperature was 1050°C, and the insulation time was 5h; the temperature was lowered from the second insulation section to the third insulation section at 20°C / min, the insulation temperature was 800°C, and the insulation time was 2h; and then cooled to room temperature to obtain the positive electrode matrix material LiNi doped with Ni and Mn. 0.09 Co 0.9 Mn 0.01 O2. The median particle size of the material tested using a laser particle size analyzer is about 20 μm.

[0035] 2) Preparation of Nano Cobalt Hydroxide Manganese Additive

[0036] Prepare a mixed salt solution of cobalt and manganese sulfate in a metal molar ratio of 9:1. The concentration of the mixed salt solution is about 2 mol / L. Then add ionized water and sodium hydroxide solution to the reactor, turn on the heating, protect with nitrogen atmosphere, set the temperature to 50°C, and start stirring the reactor. After that, start feeding the mixed sulfate solution of cobalt and manganese at a rate of about 3L / h. During the process, sample and test the pH every hour until it reaches 12.3-12.7. After the synthesis is completed, the mother liquor is separated. Pour the slurry into a Buchner funnel for suction filtration and solid-liquid separation, and then rinse the material with deionized water above 60°C. The amount of washing water is about 20 times the amount of solid. After the filtration is completed, take out the filter cake, place it in an 80°C oven, dry it for about 2-4 hours, crush it with a universal crusher, pass it through a 200-mesh sieve, and remember the prepared Co 0.9 Mn 0.1 (OH)2.

[0037] 3) Preparation of positive electrode materials for lithium-ion batteries

[0038] Lithium hydroxide, Co 0.9 Mn0.1 (OH)2 was mixed according to the molar ratio of lithium to metal of 1.05, and the mixed material was mixed with the above-mentioned positive electrode matrix material LiNi 0.09 Co 0.9 Mn 0.01 O2 is mixed with Co 0.9 Mn 0.1 The amount of Co in (OH)2 accounts for the total amount of LiNi 0.09 Co 0.9 Mn 0.01 The mass fraction of Co in O2 is 1.0%. The mixed raw materials are heated from room temperature to the first insulation section at 5℃ / min, the insulation temperature is 700℃, and the insulation time is 1h; the temperature is raised from the first insulation section to the second insulation section at 3℃ / min, the insulation temperature is 900℃, and the insulation time is 1h; the temperature is lowered from the second insulation section to the third insulation section at 20℃ / min, the insulation temperature is 800℃, and the insulation time is 1h; and then cooled to room temperature to obtain the positive electrode material. The median particle size of the material tested by the laser particle size analyzer is about 20μm.

[0039] Using N-methylpyrrolidone as solvent, the powder obtained after sintering was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 90:5:5 and then coated on the surface of clean aluminum foil and scraped to form a film. After air drying, the electrode sheet was punched into a disc with a diameter of 8 mm, and further dried in a vacuum oven at 120°C for 6 hours to remove moisture. The prepared electrode sheet was used as the working electrode of the half-cell, metallic lithium was used as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (the weight ratio of EC and DMC was 1:1) was used as the electrolyte. The battery was assembled in a glove box and the battery was charged and discharged. The voltage range was 2.8-4.4V and the charge and discharge current density was 0.1C.

[0040] Example 2

[0041] 1) Preparation of positive electrode matrix material

[0042] Preparation of Ni by co-precipitation method 0.7 Co 0.28 Mn 0.018 La 0.002 (OH)2, in which Ni and Co are evenly distributed in Ni 0.7 Co 0.28 Mn 0.018 La 0.002 In the (OH)2 matrix, Mn and La are only distributed in Ni 0.7 Co 0.28 Mn 0.018 La 0.002 (OH)2 surface 0-2μm.

[0043] Lithium hydroxide and Ni0.7 Co 0.28 Mn 0.018 La 0.002 (OH)2 is mixed according to the molar ratio of lithium to metal of 1.05, and the mixed raw materials are heated from room temperature to the first insulation section at 1°C / min, the insulation temperature is 400°C, and the insulation time is 5h; the temperature is raised from the first insulation section to the second insulation section at 1°C / min, the insulation temperature is 850°C, and the insulation time is 15h; the temperature is lowered from the second insulation section to the third insulation section at 1°C / min, the insulation temperature is 600°C, and the insulation time is 5h; and then cooled to room temperature to obtain the positive electrode matrix material LiNi doped with Ni and Mn. 0.7 Co 0.28 Mn 0.018 La 0.002 O2. The median particle size of the material tested using a laser particle size analyzer is about 20 μm.

[0044] 2) Preparation of Nano Cobalt Manganese La Hydroxide Additive

[0045] Prepare a mixed salt solution of cobalt, manganese and lanthanum sulfates according to a metal molar ratio of 9.00:0.99:0.01. The concentration of the mixed salt solution is about 2 mol / L. Then add ionized water and sodium hydroxide solution to the reactor, turn on the heating, protect with nitrogen atmosphere, set the temperature to 50°C, and start stirring the reactor. After that, start feeding the mixed sulfate solution of cobalt, manganese and lanthanum at a rate of about 3L / h. During the process, sample and test the pH every hour until it reaches 12.3-12.7. After the synthesis is completed, the mother liquor is separated. Pour the slurry into a Buchner funnel for suction filtration and solid-liquid separation, and then rinse the material with deionized water above 60°C. The amount of washing water is about 20 times the amount of solids. After the filtration is completed, take out the filter cake, place it in an oven at 80°C, dry it for about 2-4h, crush it with a universal crusher, pass it through a 200-mesh sieve, and remember the prepared Co 0.900 Mn 0.099 La 0.001 (OH)2.

[0046] 3) Preparation of positive electrode materials for lithium-ion batteries

[0047] Lithium hydroxide, Co 0.900 Mn 0.099 La 0.001 (OH)2 was mixed according to the molar ratio of lithium to metal of 1.05, and the mixed material was mixed with the above-mentioned positive electrode matrix material LiNi 0.7 Co 0.28 Mn 0.018 La 0.002 O2 is mixed with Co 0.900 Mn 0.099 La 0.001 The amount of Co in (OH)2 accounts for the total amount of LiNi 0.7Co 0.28 Mn 0.018 La 0.002 The mass fraction of Co in O2 is 0.05%. The mixed raw materials are heated from room temperature to the first insulation section at 1°C / min, the insulation temperature is 400°C, and the insulation time is 5h; the temperature is raised from the first insulation section to the second insulation section at 1°C / min, the insulation temperature is 700°C, and the insulation time is 15h; the temperature is lowered from the second insulation section to the third insulation section at 1°C / min, the insulation temperature is 600°C, and the insulation time is 5h; and then cooled to room temperature to obtain the positive electrode material. The median particle size of the material tested by a laser particle size analyzer is about 20μm.

[0048] Using N-methylpyrrolidone as solvent, the powder obtained after sintering was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 90:5:5 and then coated on the surface of clean aluminum foil and scraped to form a film. After air drying, the electrode sheet was punched into a disc with a diameter of 8 mm, and further dried in a vacuum oven at 120°C for 6 hours to remove moisture. The prepared electrode sheet was used as the working electrode of the half-cell, metallic lithium was used as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (the weight ratio of EC and DMC was 1:1) was used as the electrolyte. The battery was assembled in a glove box and the battery was charged and discharged. The voltage range was 2.8-4.4V and the charge and discharge current density was 0.1C.

[0049] Example 3

[0050] 1) Preparation of positive electrode matrix material

[0051] Preparation of Ni by co-precipitation method 0.7 Co 0.28 Mn 0.018 La 0.002 (OH)2, in which Ni and Co are evenly distributed in Ni 0.7 Co 0.28 Mn 0.018 La 0.002 In the (OH)2 matrix, Mn and La are only distributed in Ni 0.7 Co 0.28 Mn 0.018 La 0.002 (OH)2 surface 0-2μm.

[0052] Lithium hydroxide and Ni 0.7 Co 0.28 Mn 0.018 La 0.002(OH)2 was mixed according to the molar ratio of lithium to metal of 1.05, and the mixed raw materials were heated from room temperature to the first insulation section at 3°C / min, the insulation temperature was 550°C, and the insulation time was 3h; the temperature was raised from the first insulation section to the second insulation section at 2°C / min, the insulation temperature was 950°C, and the insulation time was 10h; the temperature was lowered from the second insulation section to the third insulation section at 5°C / min, the insulation temperature was 700°C, and the insulation time was 2h; and then cooled to room temperature to obtain the positive electrode matrix material LiNi doped with Ni and Mn. 0.7 Co 0.28 Mn 0.018 La 0.002 O2. The median particle size of the material tested using a laser particle size analyzer is about 20 μm.

[0053] 2) Preparation of Nano Cobalt Manganese La Hydroxide Additive

[0054] Prepare a mixed salt solution of cobalt, manganese and lanthanum sulfates according to a metal molar ratio of 9.00:0.99:0.01. The concentration of the mixed salt solution is about 2 mol / L. Then add ionized water and sodium hydroxide solution to the reactor, turn on the heating, protect with nitrogen atmosphere, set the temperature to 50°C, and start stirring the reactor. After that, start feeding the mixed sulfate solution of cobalt, manganese and lanthanum at a rate of about 3L / h. During the process, sample and test the pH every hour until it reaches 12.3-12.7. After the synthesis is completed, the mother liquor is separated. Pour the slurry into a Buchner funnel for suction filtration and solid-liquid separation, and then rinse the material with deionized water above 60°C. The amount of washing water is about 20 times the amount of solids. After the filtration is completed, take out the filter cake, place it in an oven at 80°C, dry it for about 2-4h, crush it with a universal crusher, pass it through a 200-mesh sieve, and remember the prepared Co 0.900 Mn 0.099 La 0.001 (OH)2.

[0055] 3) Preparation of positive electrode materials for lithium-ion batteries

[0056] MgF2, La2O3 and Co 0.900 Mn 0.099 La 0.001 (OH)2, and the mixed material and the positive electrode matrix material LiNi 0.7 Co 0.28 Mn 0.018 La 0.002O2 is mixed, wherein F occupies the matrix. The mixed raw materials are heated from room temperature to the first insulation section at 3°C / min, the insulation temperature is 550°C, and the insulation time is 3h; the temperature is raised from the first insulation section to the second insulation section at 2°C / min, the insulation temperature is 850°C, and the insulation time is 5h; the temperature is lowered from the second insulation section to the third insulation section at 5°C / min, the insulation temperature is 700°C, and the insulation time is 2h; and then cooled to room temperature to obtain the positive electrode material. The median particle size of the material tested by a laser particle size analyzer is about 20μm.

[0057] Using N-methylpyrrolidone as solvent, the powder obtained after sintering was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 90:5:5 and then coated on the surface of clean aluminum foil and scraped to form a film. After air drying, the electrode sheet was punched into a disc with a diameter of 8 mm, and further dried in a vacuum oven at 120°C for 6 hours to remove moisture. The prepared electrode sheet was used as the working electrode of the half-cell, metallic lithium was used as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (the weight ratio of EC and DMC was 1:1) was used as the electrolyte. The battery was assembled in a glove box and the battery was charged and discharged. The voltage range was 2.8-4.4V and the charge and discharge current density was 0.1C.

[0058] Comparative Example 1

[0059] 1) Preparation of positive electrode materials

[0060] Take lithium carbonate and Co(OH)2, mix them according to the molar ratio of lithium to metal of 1.05, raise the temperature from room temperature to the first insulation section at 5℃ / min, the insulation temperature is 700℃, and the insulation time is 3h; raise the temperature from the first insulation section to the second insulation section at 1℃ / min, the insulation temperature is 1050℃, and the insulation time is 10h; cool down from the second insulation section to the third insulation section at 5℃ / min, the insulation temperature is 800℃, and the insulation time is 2h; then cool to room temperature to obtain the positive electrode matrix material LiCoO2. The median particle size of the material tested by the laser particle size analyzer is about 20μm.

[0061] 2) Preparation of Nano-cobalt Manganese Hydroxide

[0062] Prepare a mixed salt solution of cobalt and manganese sulfate in a metal molar ratio of 9:1. The concentration of the mixed salt solution is about 2 mol / L. Then add ionized water and sodium hydroxide solution to the reactor, turn on the heating, protect with nitrogen atmosphere, set the temperature to 50°C, and start stirring the reactor. After that, start feeding the mixed sulfate solution of cobalt and manganese at a rate of about 3L / h. During the process, sample and test the pH every hour until it reaches 12.3-12.7. After the synthesis is completed, the mother liquor is separated. Pour the slurry into a Buchner funnel for suction filtration and solid-liquid separation, and then rinse the material with deionized water above 60°C. The amount of washing water is about 20 times the amount of solid. After the filtration is completed, take out the filter cake, place it in an 80°C oven, dry it for about 2-4 hours, crush it with a universal crusher, pass it through a 200-mesh sieve, and remember the prepared Co 0.9 Mn 0.1 (OH)2.

[0063] 3) Preparation of positive electrode materials

[0064] Lithium hydroxide, Co 0.9 Mn 0.1 (OH)2 is mixed according to the molar ratio of lithium to metal of 1.05, and the mixed material is mixed with the above-mentioned positive electrode material matrix LiCoO2, wherein Co 0.9 Mn 0.1 The mass fraction of Co in (OH)2 in the matrix LiCoO2 is 1.0%. The mixed raw materials are heated from room temperature to the first insulation section at 5℃ / min, the insulation temperature is 700℃, and the insulation time is 3h; the temperature is raised from the first insulation section to the second insulation section at 1℃ / min, the insulation temperature is 900℃, and the insulation time is 5h; the temperature is lowered from the second insulation section to the third insulation section at 5℃ / min, the insulation temperature is 800℃, and the insulation time is 2h; and then the positive electrode material is obtained after cooling to room temperature. The median particle size of the material tested by a laser particle size analyzer is about 20μm.

[0065] Using N-methylpyrrolidone as solvent, the powder obtained after sintering was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 90:5:5 and then coated on the surface of clean aluminum foil and scraped to form a film. After air drying, the electrode sheet was punched into a disc with a diameter of 8 mm, and further dried in a vacuum oven at 120°C for 6 hours to remove moisture. The prepared electrode sheet was used as the working electrode of the half-cell, metallic lithium was used as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (the weight ratio of EC and DMC was 1:1) was used as the electrolyte. The battery was assembled in a glove box and the battery was charged and discharged. The voltage range was 2.8-4.4V and the charge and discharge current density was 0.1C.

[0066] Using N-methylpyrrolidone as solvent, the powder obtained after sintering was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 90:5:5 and then coated on the surface of clean aluminum foil and scraped to form a film. After air drying, the electrode sheet was punched into a disc with a diameter of 8 mm, and further dried in a vacuum oven at 120°C for 6 hours to remove moisture. The prepared electrode sheet was used as the working electrode of the half-cell, metallic lithium was used as the counter electrode, and 1 mol / L LiPF6 / ethylene carbonate (EC)-dimethyl carbonate (DMC) (the weight ratio of EC and DMC was 1:1) was used as the electrolyte. The battery was assembled in a glove box and the battery was charged and discharged. The voltage range was 2.8-4.4V and the charge and discharge current density was 0.1C.

[0067] Figure 1 and Figure 2 is the SEM image of the lithium ion battery positive electrode material samples prepared in Example 1 and Comparative Example 1, Figure 3 and Figure 4 EPMA images of the element Mn in the lithium ion battery positive electrode material samples prepared in Example 1 and Comparative Example 1. Through SEM and EPMA image observation, the surface of the lithium ion battery positive electrode material prepared in Example 1 can clearly see the coating formed by the enriched coating element Mn, which presents a dot-shaped coating with a certain regular shape.

[0068] The test results of the above embodiments and comparative examples are shown in Table 1, which shows the discharge specific capacity, 5C / 0.1C retention rate, cycle retention rate and capacity recovery rate after 45°C high-temperature storage of the samples in the embodiments and comparative examples.

[0069] Table 1 Lithium-ion battery performance test data

[0070]

[0071] It can be seen from the test results of the embodiments and comparative examples in the above table that the present invention pre-forms an interface element barrier layer by designing the interface of the matrix or its near surface and designing the sintering process for the positive electrode material, and utilizes the strong bond energy between elements or the repulsion formed when a large amount of doping elements M already exist in the matrix, etc. to hinder the further diffusion of the coating element M into the matrix, making it difficult for the coating element M to enter the material matrix and form interface enrichment. This structure improves the stability of the interface structure of the positive electrode material, thereby improving the electrochemical performance of the positive electrode material under high voltage or high lithium removal.

[0072] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A positive electrode material for a lithium ion battery, characterized in that: It is a lithium-containing composite oxide with the general formula of Li α Ni x Co y M z O 2-β N β , consisting of a substrate and a coating layer, wherein M is selected from at least one element of Co, Al, Mn, Ti, Zr, Sr, W, B, Mg, Y, La, Ta, and Nb, a portion of the M element is used as a doping element of the substrate, and the other portion is used as a coating element of the coating layer and is enriched within a preset depth of the substrate interface; N is selected from at least one element of P and F; 0.95≤α≤1.05, 0.0≤x≤0.70, 0≤y<1.0, 0≤z≤0.3, 0≤β≤0.

05.

2. The lithium-ion battery positive electrode material according to claim 1, characterized in that M is selected from at least one element in a +4 valence state or higher valence state, and the M element is mainly enriched in a depth range of 0-5 μm at the matrix interface; and the doping amount of the Ni element is 0.05≤x≤0.

25.

3. A method for preparing a positive electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: The steps include: 1) preparing a compound containing Ni, Co, and M elements, mixing the compound with a lithium source, performing step-wise temperature-raising sintering after the mixture is evenly mixed, and then cooling to room temperature to obtain a positive electrode matrix material; 2) preparing an additive containing Co and M elements; 3) The obtained positive electrode matrix material and the additive containing Co and M elements are dry-mixed or liquid-mixed, wherein the liquid phase is evenly mixed and then dried to achieve M element coating, and the dried material obtained after mixing is sintered in stages at a high temperature, and then cooled to room temperature to obtain the positive electrode material for lithium-ion batteries.

4. The preparation method according to claim 3, characterized in that: The compound containing Ni, Co and M elements in step 1) is one of the hydroxides, oxides, fluorides, carbonates, nitrates, acetates and alcoholates containing Ni, Co and M elements, wherein the coprecipitate hydroxide, fluoride, carbonate, nitrate, acetate or alcoholate containing Ni, Co and M elements is prepared by a coprecipitation method, and the oxide is obtained by sintering the coprecipitate under air or oxygen.

5. The preparation method according to claim 3, characterized in that: In step 1), the compound and the lithium source are mixed according to a molar ratio of lithium to all metal elements of 0.95-1.

05.

6. The preparation method according to claim 3, characterized in that: The conditions for the staged temperature rising sintering in step 1) are: in an air or oxygen atmosphere, first rise from room temperature to the first insulation section at a rate of 1-5°C / min, the insulation temperature is 400-700°C, and the insulation time is 1-5h; then rise from the first insulation section to the second insulation section at a rate of 1-3°C / min, the insulation temperature is 800-1100°C, and the insulation time is 5-15h; then cool from the second insulation section to the third insulation section at a rate of 1-20°C / min, the insulation temperature is 600-800°C, and the insulation time is 1-5h.

7. The preparation method according to claim 6, characterized in that: In step 1), the first heat preservation stage is sintered in an atmosphere with an oxygen content of ≤0.8 standard oxygen partial pressure.

8. The preparation method according to claim 3, characterized in that: The additive containing Co and M elements in step 2) is any one of nano hydroxide, nano carbonate and nano oxide containing Co and M elements and uniformly distributed.

9. The preparation method according to claim 3, characterized in that: In step 3), a compound containing a lithium source or at least one of M and N is first mixed with an additive containing Co and M elements to obtain a first mixture, wherein the molar ratio of Li element to M element in the first mixture is 0.0 to 2.0, and then the first mixture is mixed with a positive electrode matrix material to obtain a second mixture.

10. The preparation method according to claim 3, characterized in that: The conditions for the staged temperature rising sintering in step 3) are: in an air or oxygen atmosphere, first rise from room temperature to the first insulation section at a rate of 1-5°C / min, the insulation temperature is 400-700°C, and the insulation time is 1-5h; then rise from the first insulation section to the second insulation section at a rate of 1-3°C / min, the insulation temperature is 700-950°C, and the insulation time is 1-15h; then cool from the second insulation section to the third insulation section at a rate of 1-20°C / min, the insulation temperature is 600-800°C, and the insulation time is 1-5h.

Citation Information

Cited By

  • Positive electrode material, surface-reconstructed material and lithium-ion battery

    WO2026153429A1